External Ophthalmomyiasis By Sheep Nasal Bot Fly A-Rare Case Report From Tropical Region of India - Pallavi Agrawal; Varsha Yadav; Vidhi Kathiriya; Minal Kanhere (Delhi Journal of Ophthalmology)
Myiasis is infection of tissues or organs of animals or man by larvae of a fly. Ophthalmomyiasis is classified as ophthalmomyiasis externa if the larvae are present on the conjunctiva, ophthalmomyiasis interna when there is intraocular penetration of larvae and orbital/ocular ophthalmomyiasis if larvae penetrate the orbit. This condition is rare in India, with no case reports from Mumbai. We report a rare case of Ophthalmomyiasis externa in a 25 year old male who presented with sudden onset foreign body sensation in his right eye, followed by intense watering, irritation and redness since 2 hours. Visual acuity was 6/6 and N6 in both eyes. The right eye showed superficial congestion for chemosis; and no evidence of a foreign body. On detailed examination, three motile larvae were found and removed from the conjunctiva, which were later identified as larvae of Oestrus ovis (Sheep nasal botfly). The patient was started on antihistaminics and antibiotics and showed improvement within 24 hours. Our case highlights two things - firstly, the importance of early detection of this condition by creating awareness amongst ophthalmologists as being one of the causes of conjunctivitis during spring/summer seasons especially in developing countries like India; and secondly, plain irrigation of the conjunctiva is unsuccessful in washing out of the larvae.